PERSEPSI PETANI TENTANG MODAL, PEMASARAN, DAN APLIKASI “J” AGRITECH UNTUK KESEJAHTERAAN - Silaban, Martin Dennise; Paramitha, Bella; Mawaddah, Mawaddah; Mbele, Siti Hartina; Prihatin, Silverius Djuni (Social Welfare Study Program, 2024)
Abstract. Maize plays a significant role in the global economy, however this does not always correlate with the welfare of maize farmers, particularly in developing countries. Farmers often frequently encounter obstacles such as restricted access to markets that offer fair prices, and difficulties in securing adequate capital to support their agricultural activities. In this context, PT. J. aims to provide solutions to these constraints by facilitating fair market access and offering capital support to farmers. This study aims to analyze the perceptions of farmers in Blora District regarding the services provided by PT. J. and their impact on the farmers' welfare. This research employs a qualitative case study approach. Data collection methods include observation, in-depth interviews, and document analysis. The data analysis follows an interactive model consisting of four concurrent stages: data collection, data reduction, data presentation, and conclusion drawing. The validity of the data is ensured through triangulation of both data and sources. Informants for this study include three farmers and three partners. The findings indicate that farmers hold a positive perception of PT. J.’s presence, particularly with respect to improved access to capital, enhanced marketing opportunities, and increased knowledge facilitated through the J Application platform. Keywords: Farmer; Agritech company; Farmers’ Perceptions. Abstrak. Komoditas jagung memiliki peran yang sangat signifikan dalam perekonomian global, namun hal ini tidak selalu berbanding lurus dengan kesejahteraan petani jagung, khususnya di negara-negara berkembang. Petani sering kali menghadapi kendala utama seperti terbatasnya akses terhadap pasar yang menawarkan harga layak, serta kesulitan dalam memperoleh permodalan yang memadai untuk mendukung aktivitas pertanian mereka. Dalam konteks ini, PT. J hadir dengan tujuan untuk memberikan solusi terhadap kendala-kendala tersebut melalui fasilitasi akses pasar yang adil dan penyediaan dukungan permodalan bagi para petani. Penelitian ini bertujuan untuk menganalisis persepsi petani di Kabupaten Blora terhadap layanan yang disediakan oleh PT. J serta dampak layanan tersebut terhadap kesejahteraan petani. Penelitian ini menggunakan pendekatan kualitatif studi kasus. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Analisis data dilakukan melalui model interaktif yang mencakup empat tahapan: pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data melalui triangulasi data dan triangulasi sumber. Informan dalam penelitian ini terdiri dari tiga orang petani dan tiga mitra PT. J. Hasil penelitian memperlihatkan bahwa petani memiliki persepsi positif akan hadirnya PT. J., terutama dalam hal akses permodalan, pemasaran, serta peningkatan pengetahuan melalui platform Aplikasi J. Kata Kunci: Petani, Perusahaan Agritech, Persepsi Petani.